Comparative Study On Childfree Marriage In Some Selected Countries - Yazid, Afthon; Karimullah, Suud Sarim; Sugitanata, Arif (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Childfree is a phenomenon that refers to a couple's decision not to have children, either voluntarily or temporarily. This phenomenon has become a significant topic of discussion in various countries and has become part of a global issue, including Indonesia. This issue is significant and debatable in society. In the context of the Islamic religion, having children is considered God's will, and children should be looked after properly. In societies that adhere to pronatalist views, the child-free phenomenon often faces pressure and stigmatism. However, these decisions often arise due to social, economic, and cultural changes. This research applies qualitative methods by analysing relevant literature about the childfree phenomenon. This research aims to review the factors behind the choice to be child-free in various countries. The research results show that many factors, including personal, economic, and environmental factors, influence the decision not to have children. In Indonesia, childfree still needs to be fully implemented, and the reason for choosing childfree is motivated by economic considerations. Meanwhile, abroad, the influence of childlessness is more varied, ranging from personal, economic, environmental, and psychological factors. Further research into the childfree phenomenon is needed to better understand its impact on families and society.